An atypical presentation of immune checkpoint inhibitor associated myositis with normal creatine kinase: a case report - Satoskar, Monika A.; Mansour, Anthony G.; Wu, Richard; Yang, Yuanquan; Caldwell, Mary H.; Meara, Alexa S. (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) have been revolutionary in the field of cancer therapeutics. Myositis is a known rheumatic immunotherapy related adverse event with a fatality rate of 26.8% when associated with myasthenia gravis and 51.3% when associated with myocarditis. Typically, creatine kinase (CK) is elevated in ICI-myositis, thus normal CK levels in such cases may delay diagnosis and treatments in such patients. We report 2 cases of patients diagnosed with ICI-myositis after ipilimumab/nivolumab treatment for metastatic renal cell carcinoma and metastatic melanoma. Their lab studies showed normal CK values but elevated aldolase, which led to the ICI-myositis diagnosis and steroid treatment. Early recognition and treatment with steroids led to symptom improvement. These 2 cases highlight an atypical presentation of ICI-myositis with normal CK but elevated aldolase levels, suggesting aldolase may be a sensitive parameter in diagnosing ICI-myositis.